2022
DOI: 10.3390/foods11040500
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiling in Kernels Coupled with Chemometric Analyses as a Feasible Strategy for the Discrimination of Different Walnuts

Abstract: Walnuts have high oil content in their kernels, and they have attracted considerable attention in the food, beverage, nutrient, and health fields because of their delicious taste and potential health benefits. Fatty acid profiles of kernels vary depending on walnuts species, ontogenic variations, and planting environments. To determine the key indicators that can be used to distinguish different walnuts using chemometric analyses, the fatty acid compositions and contents of 72 walnut samples were measured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Walnuts are rich sources of polyunsaturated fatty acids, such as linoleic acid (LA, C18:2n-6) and alpha-linolenic acid (ALA, C18:3n-3) [ 40 ]. Accumulating evidence has shown that LA has neuroprotective properties.…”
Section: Anti-inflammatory Components Of Walnutsmentioning
confidence: 99%
“…Walnuts are rich sources of polyunsaturated fatty acids, such as linoleic acid (LA, C18:2n-6) and alpha-linolenic acid (ALA, C18:3n-3) [ 40 ]. Accumulating evidence has shown that LA has neuroprotective properties.…”
Section: Anti-inflammatory Components Of Walnutsmentioning
confidence: 99%
“…Walnut (Juglans regia L.) is a tree that can be found naturally in many parts of the world (including Asia, Europe and the Americas) [1,2]. It owes its popularity to tasty and healthy fruits rich in polyunsaturated fatty acids, including alpha-linolenic acid [3,4]. Additionally, walnuts are a source of easily digestible iron, magnesium, sodium and potassium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed this belief, showing that walnut supplements can reduce the risk of neurodegenerative diseases and delay their onset and progression [ 9 ]. Walnuts are a rich source of polyunsaturated fatty acids such as linoleic acid (LA; C18:2ω-6) and alpha-linolenic acid (ALA; C18:3ω-3) [ 10 ]. Accumulating evidence shows that LA and ALA have neuroprotective properties.…”
Section: Introductionmentioning
confidence: 99%